Safety and efficacy of different lanreotide doses in the treatment of polycystic liver disease: pooled analysis of individual patient data. Issue 4 (25th June 2013) - Temmerman, F.; Gevers, T.; Ho, T. A.; Vanslembrouck, R.; Coudyzer, W.; van Pelt, J.; Bammens, B.; Pirson, Y.; Drenth, J. P.; Nevens, F.
Summary: Background: Long‐acting lanreotide (LAN) 120 mg every 4 weeks reduces liver volume (LV) in patients with polycystic liver diseases (PCLD). Animal studies demonstrated that the inhibition of hepatic and renal cystogenesis is dose dependent. Aim: To investigate the safety and efficacy of two different LAN doses in PCLD patients. Methods: The 6‐month results of the LOCKCYST I trial, its extension study and the LOCKCYST II trial were pooled. LV at baseline and month 6 was measured by CT‐scan and blindly re‐analysed by two independent radiologists. Results: The study population [132 treatment periods, age 49 years (IQR: 45‐55), 114 women] consisted of three groups. Each received treatment every 4 weeks during 6 months: placebo ( n = 26); LAN 90 mg ( n = 55) or LAN 120 mg ( n = 51). The inter‐observer variability and agreement in the calculation of LV were excellent. Severe side effects occurred with placebo, LAN 90 mg and LAN 120 mg in respectively 0%, 7% and 16%. Change in LV's after 6 months in these three groups were respectively: increase of +36 mL [(−45)–(+138)]; decrease of −82 mL [(−285)–(+92)] and decrease of ‐123 mL [(−312)–(+4)] (Kruskal‐Wallis One Wayanova on Ranks; P = 0.002). Based on ROC analysis, a reduction of ≥120 mL in LV has a positive predictive value of 64% for improving symptoms (ROC analysis AUC: 0.729; sensitivity 73%, specificity 69%, P < 0.0001). Conclusions: Both LAN 90 mg and LAN 120 mg reduce liver volume. LAN 90 mg has less side effects. This suggests that in case of intolerance to LAN 120 mg, a dose reduction to LAN 90 mg is meaningful.